2006
DOI: 10.1194/jlr.m600140-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of liver VLDL receptor and FAT/CD36 expression in LDLR−/− apoB100/100 mice fed trans-10,cis-12 conjugated linoleic acid

Abstract: This study explores the mechanisms responsible for the fatty liver setup in mice fed trans-10,cis-12 conjugated linoleic acid (t10c12 CLA), hypothesizing that an induction of low density lipoprotein receptor (LDLR) expression is associated with lipid accumulation. To this end, the effects of t10c12 CLA treatment on lipid parameters, serum lipoproteins, and expression of liver lipid receptors were measured in LDLR 2/2 apoB 100/100 mice as a model of human familial hypercholesterolemia itself depleted of LDLR. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 43 publications
9
57
0
Order By: Relevance
“…Previous studies have shown that L-FABP-deficient mice manifest decreased fatty acid binding capacity and are protected against obesity-induced hepatic steatosis (34). On the other hand, FAT/CD36 is markedly overexpressed in the liver of ob/ob mice and its mRNA levels increase in parallel with liver TG content in experimental fatty liver (36,37). Therefore, our results showing a reduction in L-FABP and FAT/CD36 after 5-LO inhibition contribute to explain the overall antisteatotic action of this experimental maneuver in ob/ob mice.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that L-FABP-deficient mice manifest decreased fatty acid binding capacity and are protected against obesity-induced hepatic steatosis (34). On the other hand, FAT/CD36 is markedly overexpressed in the liver of ob/ob mice and its mRNA levels increase in parallel with liver TG content in experimental fatty liver (36,37). Therefore, our results showing a reduction in L-FABP and FAT/CD36 after 5-LO inhibition contribute to explain the overall antisteatotic action of this experimental maneuver in ob/ob mice.…”
Section: Discussionmentioning
confidence: 91%
“…To gain further insight into the pathogenesis of NAFLD in the ICD-E mice we therefore examined liver transcription at 6 and 24 hour time points, using expression microarrays. Transcription of two genes involved in fatty acid uptake were up-regulated at 6 hours post-induction (Table 1); Abcd2 , a gene known to be involved in the peroxisomal import of fatty acids [37], and the very low density lipoprotein receptor ( Vldlr ) [38]. It is also interesting to note that a previous report has indicated that Abcd 2 suppresses transcription of the fatty acyl chain elongase Elovl3 and this was supported by our data at all time points [39].…”
Section: Resultsmentioning
confidence: 99%
“…The fact that FAT/CD36 was not modified by ROSI likely concurs with its dramatically low expression level in the liver of normal mice. Ectopic induction of FAT/CD36 occurs in the liver when cells are supplied with a high FA flux causing TG accumulation [31] suggesting a specific PPARγ activation pathway that did not concern our model. Conversely, as PIO treatment did not modify the expression of PPARγ and related genes, it can be reasoned that the effects of PIO on lipid metabolism are PPARγ -independent.…”
Section: Discussionmentioning
confidence: 99%
“…Total mRNA was reverse-transcripted using the Iscript cDNA kit (Bio-Rad, Marnes-La Coquette, France). Real-time polymerase chain reaction was performed as described previously [31] in a 96-well plate using an iCycler iQ (Bio-Rad). The sequences of the forward and reverse primers used are described in Table 1.…”
Section: Gene Expressionmentioning
confidence: 99%